ANALISIS PENGELUARAN PELAYANAN DASAR DI 508 KABUPATEN/KOTA PADA PERIODE DESENTRALISASI 2007-2020 - Randy Febriatama (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
Decentralization is the best system for providing basic services such as education, health, and infrastructure. Fiscal decentralization has been implemented for two decades with a marked increase in transfers and regional revenue autonomy. The magnitude of the increase in the regional fiscal capacity should give local governments the flexibility to provide for the community's basic needs. This study aims to see the impact of fiscal decentralization on basic spending. The data used is panel data in the form of 508 Regencies/Cities during 2007-2020. The multiple linear regression model shows that the General Allocation Fund, the Special Allocation Fund, the Revenue Sharing Fund, and Regional Taxes significantly affect basic service spending.